The Correlation between Sexual Dysfunction and Marital Relationship among Women with Gynaecological Problems - Nurhayati, Nunung; Ulsiyah, Utami Nur; Noor, Suci; Marfuah, Dewi; Lindayani, Linlin (Jurusan Keperawatan FIKES UNSOED, 2021)
Women with gynaecological problems are at high risk of having sexual dysfunction because the problems could affect the marital relationship and sexual satisfaction. The purpose of this study is to determine the relationship between sexual dysfunction and marital relationships in women with gynaecological problems. This study was conducted using a cross-sectional study. The samples were women with gynaecological problems, aged above 18 years old, married, and able to communicate well. Patients with mental disorders were excluded from this study. Convenience sampling was used to select participants. The marital relationship was measured using a validated instrument, namely, Revised Dyadic Adjustment Scale (RDAS) and the Female Sexual Function Index (FSFI). A total of 82 women with gynaecological problems joined our study. The majority of the respondents experienced sexual dysfunction (90.2%) and more than half of the respondents (52.4%) experienced distress in marital relationships.Â There was a relationship between sexual dysfunction and marital relationship among women with gynaecological problems (p value < 0.005) and the coefficient correlation was 0.326. Sexual dysfunction may affect marital relationships in women with gynaecological problems. Healthcare professionals need to provide appropriate intervention to women with gynaecological problems as well as facilitate them to express their sexual activity.